A roadmap to ISO 14971 implementation. Issue 5 (14th April 2015) - Flood, Derek; McCaffery, Fergal; Casey, Valentine; McKeever, Ruth; Rust, Peter
Abstract Medical device standards outline the requirements for developing medical devices. These standards, however, do not outline how these requirements should be implemented causing difficulties for organisations entering the medical device domain. The goal of this study is to validate a roadmap for the implementation of the ISO 14971 standard. The validation examined the arrangement of the milestones within the roadmap and grouping of the goals into milestones. Five experienced risk management personnel in the medical device domain were asked to complete an online questionnaire examining their opinion on the structure and content of the roadmap. Overall participants found the roadmap, in general, to be well structured and well organised and made some recommendations for improving the roadmap through merging of specific goals and rearrangement of the milestones within the roadmap. Copyright © 2015 John Wiley & Sons, Ltd.